2023
DOI: 10.1002/alz.12961
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics profiling of human plasma and cerebrospinal fluid reveals ATN‐derived networks and highlights causal links in Alzheimer's disease

Abstract: IntroductionThis study employed an integrative system and causal inference approach to explore molecular signatures in blood and CSF, the amyloid/tau/neurodegeneration [AT(N)] framework, mild cognitive impairment (MCI) conversion to Alzheimer's disease (AD), and genetic risk for AD.MethodsUsing the European Medical Information Framework (EMIF)‐AD cohort, we measured 696 proteins in cerebrospinal fluid (n = 371), 4001 proteins in plasma (n = 972), 611 metabolites in plasma (n = 696), and genotyped whole‐blood (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Cerebrospinal fluid (CSF) serves as a protective barrier for the central nervous system (CNS) and analyzing CSF proteome can contribute to the diagnosis of various CNS-related diseases, but our understanding of robust AD-specific CSF proteome alterations is currently limited. 87 , 88 While numerous CSF proteomics investigations have focused on AD, 14 19 , 22 , 23 none have examined a cohort of this magnitude (7,029 proteins in 2,286 individuals), thus hindering their ability to identify consistent proteomic changes and construct a reliable predictive model. Although previous studies have identified several novel protein markers for AD, most of which were also replicated in our analyses, their major limitations were the limited coverage of the proteome and relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cerebrospinal fluid (CSF) serves as a protective barrier for the central nervous system (CNS) and analyzing CSF proteome can contribute to the diagnosis of various CNS-related diseases, but our understanding of robust AD-specific CSF proteome alterations is currently limited. 87 , 88 While numerous CSF proteomics investigations have focused on AD, 14 19 , 22 , 23 none have examined a cohort of this magnitude (7,029 proteins in 2,286 individuals), thus hindering their ability to identify consistent proteomic changes and construct a reliable predictive model. Although previous studies have identified several novel protein markers for AD, most of which were also replicated in our analyses, their major limitations were the limited coverage of the proteome and relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have identi ed several novel protein markers for AD, most of which were also replicated in our analyses, their major limitations were the limited coverage of the proteome and relatively small sample size. Moreover, relatively fewer studies have covered the entire AD continuum, [14][15][16][17][18] as many of them omitted the asymptomatic (A + T -) or mild cognitive impairment (MCI) stage, which is crucial for identifying early biomarkers for AD. In-depth CSF proteomic pro ling of AD patients and controls has the potential to uncover disease-speci c proteomic alterations, provide insights into the underlying biological processes, and translate these multifaceted ndings into practical disease prediction models for better and early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, multi-omics approaches allowed us to improve the characterization of COVID-19 infection, identifying both predictive biomarkers of severity [ 103 ] and anti-inflammatory response [ 104 ]. A similar strategy has been applied to investigate possible biomarkers of neurological diseases [ 105 , 106 , 107 ] and metabolic disorders [ 108 , 109 , 110 ]. However, the initial stage of sample collection and handling still represents a bottleneck for large-cohort and long-term studies [ 111 ].…”
Section: Microsampling Applications Monitoring Lipids and Metabolitesmentioning
confidence: 99%
“…1 The primary objective of this profile is to define AD as a biological construct independently of clinical status, thereby improving the understanding of the sequence of AD events in a more precise approach. 1 Since then, this profile has been utilized in many studies for different research purposes in AD, including exploration of the concordance and discordance between the A/T/N profile and clinical diagnosis, [2][3][4] investigation of the association between the A/T/N profile and cognitive change, 3,[5][6][7] the risk of mortality, 8 and the risk factor, 9,10 detection of the changes of ADrelated markers over the A/T/N profiles, 6,[11][12][13][14] and the use of the A/T/N biomarkers alone or in combination to determine optimal diagnostic markers. 15,16 With the development of high-performing assays for plasma biomarkers, increasing studies have investigated plasmarelated A/T/N biomarkers against the pathological outcome based on PET or CSF biomarkers.…”
Section: Introductionmentioning
confidence: 99%